An introduction to Japanese society - Sugimoto, Yoshio, 1939- (Contemporary Japanese society., 2003)
In a second edition of his book which has become essential reading for all students of Japanese society, Sugimoto updates and expands on his original narrative. In so doing he challenges the notion that Japan comprises a uniform culture and draws attention to its subcultural diversity.